Recurrence, Reactivation, or Inflammatory Rebound of SARS-CoV-2 Infection With Acute Vestibular Symptoms: A Case Report and Revision of Literature - Zaffina, Salvatore; Lanteri, Paola; Gilardi, Francesco; Garbarino, Sergio; Santoro, Annapaola; Vinci, Maria Rosaria; Carsetti, Rita; Scorpecci, Alessandro; Raponi, Massimiliano; Magnavita, Nicola; Camisa, Vincenzo (Frontiers in Human Neuroscience, 2021)
A case of recurrent coronavirus 19 disease (COVID-19) with neurovestibular symptoms is reported. In March 2020, a physician working in an Italian pediatric hospital had flu-like symptoms with anosmia and dysgeusia and tested positive for SARS-CoV-2 at RT/PCR on naso-pharingeal swab. After home quarantine, 21 days from the beginning of the symptoms, the patient tested negative in two subsequent swabs, was declared healed and readmitted to work. Serological testing showed low level of IgG antibody title and absence of IgM. However, two weeks later, before resuming work, the patient complained of acute vestibular syndrome and RT/PCR test on mucosal swab turned positive. On the basis of the literature examined and reviewed for recurrence cases and vestibular symptoms during COVID-19, to our knowledge this case is the first case of recurrence with vestibular impairment as neurological symptom and we defined it as probably a viral re-activation. The PCR retest positivity cannot differentiate re-infectivity, relapse, and dead-viral RNA detection, serological antibody testing, and viral genome sequencing could be always performed in recurrence cases.